Political Party Brand Competence and Voters’ Decision Making In Nigeria - Austine Opara, Adiele (British Journal of Marketing Studies, 2022)
Citation: Adiele Austine Opara (2021) Political Party Brand Competence and Voters’ Decision Making In Nigeria, British Journal of Marketing Studies, Vol. 10, Issue 1, pp.13-31 Abstract: This study examined the relationship between political party brand competence and voters’ decision making in Nigeria. The study adopted a cross-sectional survey in its investigation of the variables. Primary data was generated through structured questionnaire. The target population of this study was eighty four million, four thousand and eighty four (84,004, 084). Given an accessible population of twenty six million, six hundred and thirty four thousand six hundred and five (26,634,605) within the six geo-political zones in Nigeria, the sample size of 384 was determined using calculated using the Taro Yamane’s formula for sample size determination. The reliability of the instrument was achieved by the use of the Cronbach Alpha coefficient with all the items scoring above 0.70. The hypotheses were tested using the Pearson Product Moment Correlation Coefficient with the aid of Statistical Package for Social Sciences version 23.0. The tests were carried out at a 95% confidence interval and a 0.05 level of significance. The findings revealed that there is a significant political party brand competence and voters’ decision making in Nigeria. The study concludes that when political parties adopt and build brand competence it has a positive influence on voters’ decision making in Nigeria. The study recommends that political parties should always present brands (candidates) for elective positions based on personality of such candidates especially with regards to brand competence.